2004
DOI: 10.1021/nl049361t
|View full text |Cite
|
Sign up to set email alerts
|

Shadow Nanosphere Lithography:  Simulation and Experiment

Abstract: In this letter we describe the preparation of large-area, two-dimensional metallic structures using shadow nanosphere lithography. By varying the position of the substrate with respect to the evaporation source during the sample preparation, we make morphologies such as cups, rods, and wires, that are not accessible by the standard nanosphere lithography. This technique also allows for an encapsulation of the metallic structures, to prevent them from oxidation. Morphologies predicted by our computer simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
287
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(289 citation statements)
references
References 12 publications
(14 reference statements)
2
287
0
Order By: Relevance
“…For a more detailed description of the process, we refer to Ref. 10 and will give only a short summary here. We used monodisperse PS spheres with a diameter of 470 nm as a mask template.…”
Section: Methodsmentioning
confidence: 99%
“…For a more detailed description of the process, we refer to Ref. 10 and will give only a short summary here. We used monodisperse PS spheres with a diameter of 470 nm as a mask template.…”
Section: Methodsmentioning
confidence: 99%
“…11). By rotating substrates, Giersig and coworkers have recently found that AR-NSL can generate much more complicate metallic nanostructures and they referred to this process as shadow NSL [43,68,69]. Zhang and Wang have recently demonstrated the feasibility of consecutively depositing two different metals, such as gold and silver, at two different incidence angles, to construct ordered binary arrays of gold and silver nanoparticles [70].Due to the rotation of the colloidal mask, shadow NSL relies in a process resolved by the azimuth angle (ϕ) of the incidence deposition beam rather than the incidence angle (θ).…”
Section: Colloidal Masks-assisted Physical Depositionmentioning
confidence: 99%
“…The group of Van Duyne has succeeded in growth of surface patterning features composed of two triangular nanodots either overlapped or separated by two deposition steps at θ = 0º and θ > 0º, respectively [65]. Giersig et al have also developed a stepwise shadow NSL protocol to deposit different materials at different incidence angles when the colloidal masks were rotating and they have succeeded in encapsulation of the metallic structures to prevent them from oxidation [69].…”
Section: Colloidal Masks-assisted Physical Depositionmentioning
confidence: 99%
“…This technique exploits the periodic nature of a hexagonally close-packed (hcp) monolayer of nanometerto micrometer-sized polystyrene spheres (PSSs) as a lithographic mask for physical and/or electrochemical material deposition, wet and dry etching processes, and any possible combination thereof [9][10][11][12][13]. Such hcp monolayers of PSSs can be created by dip-coating, electrophoretic deposition, spin-coating, and interface assembly techniques [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that this shadow effect can be exploited to fabricate further sophisticated nanostructures such as nanowires, nanorings, and nano split-ring resonators [9,10].…”
mentioning
confidence: 99%